Impact of HIV infection on the presentation, outcome and host response in patients admitted to the intensive care unit with sepsis; a case control study. Issue 1 (December 2016) - Wiewel, Maryse; Huson, Michaëla; van Vught, Lonneke; Hoogendijk, Arie; Klein Klouwenberg, Peter; Horn, Janneke; Lutter, René; Cremer, Olaf; Schultz, Marcus; Bonten, Marc; van der Poll, Tom
Abstract Background Sepsis is a prominent reason for intensive care unit (ICU) admission in patients with HIV. We aimed to investigate the impact of HIV infection on presentation, outcome and host response in sepsis. Methods We performed a prospective observational study in the ICUs of two tertiary hospitals. For the current analyses, we selected all patients diagnosed with sepsis within 24 hours after admission. Host response biomarkers were analyzed in a more homogeneous subgroup of admissions involving HIV-positive patients with pneumosepsis, matched to admissions of HIV-negative patients for age, gender and race. Matching was done by nearest neighbor matching with R package "MatchIt". Results We analyzed 2251 sepsis admissions including 41 (1.8 %) with HIV infection (32 unique patients). HIV-positive patients were younger and admission of HIV-positive patients more frequently involved pneumonia (73.2 % versus 48.8 % of admissions of HIV-negative patients, P  = 0.004). Disease severity and mortality up to one year after admission did not differ according to HIV status. Furthermore, sequential plasma levels of host response biomarkers, providing insight into activation of the cytokine network, the vascular endothelium and the coagulation system, were largely similar in matched admissions of HIV-positive and HIV-negative patients with pneumosepsis. Conclusions Sepsis is more often caused by pneumonia in HIV-positive patients. HIV infection has little impact on the disease severity, mortality and host response during sepsis.